Organizational Identification in Youth and Sports Directorates: Through the relationship indicator between supervisors and non-supervisors’ achievement Motivation - Mirouh, Abdelouahab; Bouatit, Djallal eddine (sports creativity, 2025)
Organizational identification is a crucial factor in youth and sports directorates for achieving their tasks and goals, because it reflects the similarity and harmony between the objectives, values and motives of its management and workers. This field study aims to examine one aspect of organizational identification, which is the achievement motivation between supervising workers and non-supervisory workers in the Directorate of Youth and Sports in the state of Mila. The descriptive approach was applied by distributing a questionnaire of achievement motivation to the study sample that was consisted 75 supervisors and workers. Results shows a positive and strong correlation between most various dimensions of achievement motivation between supervisors and workers; however, the identification need for control was average and positive.